Inhibition of Low-Grade Inflammation by Anthocyanins after Microbial Fermentation in Vitro - Kuntz, Sabine; Kunz, Clemens; Domann, Eugen; Würdemann, Nora; Unger, Franziska; Römpp, Andreas; Rudloff, Silvia; Justus Liebig University Giessen (My University, 2016)
The anti-inflammatory effects of anthocyanins (ACNs) on vascular functions are discussed controversially because of their low bioavailability. This study was performed to determine whether microorganism (MO)-fermented ACNs influence vascular inflammation in vitro. Therefore, MO growth media were supplemented with an ACN-rich grape/berry extract and growth responses of Escherichia coli, E. faecalis and H. alvei, as well as ACN fermentation were observed. MO supernatants were used for measuring the anti-inflammatory effect of MO-fermented ACNs in an epithelial-endothelial co-culture transwell system. After basolateral enrichment (240 min), endothelial cells were stimulated immediately or after 20 h with TNF-a. Afterwards, leukocyte adhesion, expression of adhesion molecules and cytokine release were measured. Results indicate that E. coli, E. faecalis and H. alvei utilized ACNs differentially concomitant with different anti-inflammatory effects. Whereas E. coli utilized ACNs completely, no anti-inflammatory effects of fermented ACNs were observed on activated endothelial cells. In contrast, ACN metabolites generated by E. faecalis and H. alvei significantly attenuated low-grade stimulated leukocyte adhesion, the expression of adhesion molecules E-selectin, VCAM-1 and ICAM-1 and cytokine secretion (IL-8 and IL-6), as well as NF-KB mRNA expression with a more pronounced effect of E. faecalis than H. alvei. Thus, MO-fermented ACNs have the potential to reduce inflammation.
Keywords: grapes and berries; anthocyanins; low-grade inflammation; fermentation; in vitro co-culture model; ddc:570